Fatores que estruturam metacomunidades em fitotelmos de restinga - Nallis, Bruna Golinelli (2020)
Neotropical ecosystems harbour an imense biodiversity, covering phytophysiognomies with unique characteristics. The restingas are phyto-physiognomies characteristic of coastal regions, with hot temperatures, poor soils and low water availability, characteristics that make survival difficult in this region, however there are plant species that make life in these places easier. An example is the Bromeliacea family, which has species with phytothelmos capable of retaining water and organic matter, creating an opportunistic environment for other forms of life.. Considering the fact that these plants have unique characteristics to harbor other organisms, each bromeliad can be considered as a habitat patch within a metacommunity. We studied the factors responsible for the structuring of the metacommunity in two species of bromeliad: Aechmea nudicaulis (low phytotelmata heterogeneity) and Vriesea friburgensis (high phytotelmata heterogeneity) in a restinga from south Brazil. We found that communities are composed by many common and few rare invertebrate species. Only a small proportion of community composition variation (10%) was related to the explanatory factors considered, with bromeliad species and the vegetation cover index (NDVI) around the plants being the most relevant. The results also show that, contrary to expectations, bromeliads with greater habitat heterogeneity (V. friburgensis) had less species richness. Applying rank abundance models, we found that the individual communities were similar to null models, without apparent structuring by species niche processes. However, when the communities were grouped by plant species (summing the abundance of several bromeliads), we found that the Zipf and Mandelbrot models, which consider patch dynamics of colonization and extinction by generalist and specialist species, were the most suitable models. Our results demonstrate that the bromeliad communities do not behave individually as isolated systems, but rather as habitat patches within a metacommunity, whith random patch dynamics of colonization and local extinctions in a set of bromeliads. Understanding this metacommunity dynamic helps us to understand the importance of conserving restinga areas to preserve Neotropical biodiversity.